Three-dimensional computed tomographic assessment of mandibular muscles in growing subjects with different vertical facial patterns - Wong Alwyn; Woods Michael G.; Stella Damien (Sciendo, 2016)
The present study was undertaken to assess the relationship between the mandibular muscles and dentofacial skeletal morphology in children with different underlying vertical facial patterns, using three-dimensional computed tomography (3D-CT).